Knowledge Mapping of Volunteer Motivation: A Bibliometric Analysis and Cross-Cultural Comparative Study - Chen, Jing; Wang, Chengliang; Tang, Yulong (Frontiers in Psychology, 2022)
Volunteers play an indispensable role in many major events and activities. The purpose of this study is to review studies on volunteer motivation from 2000 to January 2022 and to learn the development trend of this field. Web of Science Core Collection is the main literature data resources, from which 163 papers on volunteer motivation published in SSCI were selected. With the two visualization analysis tools, CiteSpace and VOSviewer, this study conducts bibliometric analysis and systematic review from multiple dimensions, identifying the authors, countries, institutions and journals with high productivity in this field. Besides, we also explore the highly cited papers, authors and journals in this field. This study aims to find the research hotspots and theoretical basis through co-occurrence analysis and cluster analysis of keywords and explore the evolution trend through the time zone map drawn with CiteSpace. Moreover, the influence of Chinese and Western cultures (represented by China and the United States) on volunteer motivation is also our focuses. It was found that Chinese volunteers are more affected by collectivism, while American volunteers were more affected by individualism. The conclusion of this study constructs a clear framework of researches on volunteer motivation, which gives researchers a deeper and thorough understanding of the connotation of volunteer motivation, providing a guidance and support for future researches in this field.